Research on the double-layer intra-day management and control method of ring structure microgrid cluster based on multi-time scale - Ning Yan (Elsevier, 2021)
In general, a tree-like or radial connection structure is adopted by the microgrid cluster (MGC) to connect to the power grid. However, the power interaction is restricted by the bus capacity, and the management and control are complicated in the tree-like or radial connection structure. Therefore, the ring structure MGC is proposed to solve the above problems. Intra-day rolling correction method based on the ring structure MGC at different time levels is investigated in this paper. Firstly, ring connection is used to build the structure of multi-connected MGC, and power interaction between MGC is carried out through tie lines. Secondly, MG is taken as the lower layer object, and the lowest generation cost is taken as the target to control the lower level. Taking MGC as the upper layer object, the double-layer intra-day management and control model is established with consideration of the power balance and steady-state security constraints of the MGC. Finally, a lower layer control method based on the robust adaptive characteristic is proposed, which uses the asynchronous coordinated control method to modify the MGC. The ring network architecture has a good effect on energy consumption. The layered intra-day management method can effectively make up for the shortcomings of the day-ahead control, and the overall scheduling accuracy is satisfied.